Mu-opioid receptor and receptor tyrosine kinase crosstalk: Implications in mechanisms of opioid tolerance, reduced analgesia to neuropathic pain, dependence, and reward - Gamble, Mackenzie C.; Williams, Benjamin R.; Singh, Navsharan; Posa, Luca; Freyberg, Zachary; Logan, Ryan W.; Puig, Stephanie (Frontiers in Systems Neuroscience, 2022)
Despite the prevalence of opioid misuse, opioids remain the frontline treatment regimen for severe pain. However, opioid safety is hampered by side-effects such as analgesic tolerance, reduced analgesia to neuropathic pain, physical dependence, or reward. These side effects promote development of opioid use disorders and ultimately cause overdose deaths due to opioid-induced respiratory depression. The intertwined nature of signaling via μ-opioid receptors (MOR), the primary target of prescription opioids, with signaling pathways responsible for opioid side-effects presents important challenges. Therefore, a critical objective is to uncouple cellular and molecular mechanisms that selectively modulate analgesia from those that mediate side-effects. One such mechanism could be the transactivation of receptor tyrosine kinases (RTKs) via MOR. Notably, MOR-mediated side-effects can be uncoupled from analgesia signaling via targeting RTK family receptors, highlighting physiological relevance of MOR-RTKs crosstalk. This review focuses on the current state of knowledge surrounding the basic pharmacology of RTKs and bidirectional regulation of MOR signaling, as well as how MOR-RTK signaling may modulate undesirable effects of chronic opioid use, including opioid analgesic tolerance, reduced analgesia to neuropathic pain, physical dependence, and reward. Further research is needed to better understand RTK-MOR transactivation signaling pathways, and to determine if RTKs are a plausible therapeutic target for mitigating opioid side effects.